An economic explanation of the early Bank of Amsterdam, debasement, bills of exchange, and the emergence of the first central bank - Stephen Quinn; William Roberds (Federal Reserve Bank of Atlanta, 2006)
The Bank of Amsterdam, founded in 1609, was the first public bank to offer accounts not directly convertible to coin. As such, it can be described as the first true central bank. The debut of central bank money did not result from any conscious policy decision, however, but instead arose almost by accident, in response to the chaotic monetary conditions during the early years of the Dutch Republic. This paper examines the history of this momentous development from the perspective of modern monetary theory.
Keywords: E42; E52; N13; 330; money; central banks; coinage; debasement